Crural fascia and muscle origins related to medial tibial stress syndrome symptom location - Stickley, C. D.; Hetzler, R. K.; Kimura, I. F.; Lozanoff, S. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Traction-induced injury, related to muscles of the superficial and deep posterior compartments, has been implicated as the cause of medial tibial stress syndrome (MTSS) with symptoms commonly occurring in the distal third of the posteromedial tibia. Standard anatomic texts do not identify this region as an attachment site for these structures. Research into the anatomical arrangement of these structures has been inconclusive. The deep crural fascia (DCF) has been implicated as a cause of traction-induced injury in MTSS but not fully researched. The purpose of this study was to define the tibial origins of the DCF and the muscles of the superficial and deep posterior compartments relative to MTSS-related pain commonly reported along the distal one half to one third of the diaphysis of the medial tibial border and to identify the prevalence of a soleal aponeurosis.